Disabled Veteran Characters in Turkish Literature from the Armistice through the Republican Period and the Perception of Disabled Veterans - Besikci, Mehmet (ISTANBUL UNIV, 2024)
From a historian's point of view, this article focuses on how the disabled veterans of the Ten-Year War (1912-1922) were represented in Turkish literature from the Armistice through the Republican periods. Dealing specifically with novels and stories, the article discusses that the existing approach to disabled veterans, which was quite problematic in the era under study, was also reflected in the literary texts produced in this period. On the other hand, these literary texts themselves were among the factors that shaped this troubled perception. In that respect, the article underlines three main problems. First, ableist biases and the masculine perspective fed by militarist motifs led to the creation of a stereotyped disabled veteran character in literary texts; in this stereotype, disabled veterans are regarded as incompatible with the image of an ideal masculine soldier. Second, instead of being analyzed in depth within their own real and complex contexts, disabled veteran characters are usually used as auxiliary elements to strengthen a different message in the political-ideological agenda of authors and their texts. Third, as a result of ableist biases, disabled veteran characters were always obliged to achieve extraordinary duties in these literary texts, as if they needed to do this to compensate for their physical deficiencies. Though the main focus of the article is the early Republican era (1923-1946), it extends its time period until 1981; it also deals with the social realist literary perspective in order to make a comparison.
Keywords: Disabled Veteran; Ableist Biases; Ten-Year War; Perception of Disability; Turkish Literature; Area Studies; History